2020
DOI: 10.1098/rsos.200931
|View full text |Cite
|
Sign up to set email alerts
|

Why chimpanzees carry dead infants: an empirical assessment of existing hypotheses

Abstract: The study of non-human primate thanatology has expanded dramatically in recent years as scientists seek to understand the evolutionary roots of human death concepts and practices. However, observations of how conspecifics respond to dead individuals are rare and highly variable. Mothers of several species of primate have been reported to carry and continue to interact with dead infants. Such interactions have been proposed to be related to maternal condition, attachment, environmental conditions or reflect a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
63
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(74 citation statements)
references
References 56 publications
10
63
1
Order By: Relevance
“…The impact of grief on wild animal behavior and survival are much more challenging to identify in natural populations as compared to humans, but the last decade has seen efforts to identify these effects (48)(49)(50). Within the populations studied here, an example of the death of a white-faced capuchin mother from the Lomas Barbudal population is consistent with our expectations of what grief might look like in a wild primate.…”
Section: Distinguishing Between the Maternal Condition And Maternal Gsupporting
confidence: 75%
“…The impact of grief on wild animal behavior and survival are much more challenging to identify in natural populations as compared to humans, but the last decade has seen efforts to identify these effects (48)(49)(50). Within the populations studied here, an example of the death of a white-faced capuchin mother from the Lomas Barbudal population is consistent with our expectations of what grief might look like in a wild primate.…”
Section: Distinguishing Between the Maternal Condition And Maternal Gsupporting
confidence: 75%
“…Birth-related hormones cannot explain this case, although the mechanisms through which siblings bond may be a factor. Dead infant carrying by non-mothers has also been reported for geladas (Fashing et al 2011 ), gorillas (Warren and Williamson 2004 ), chimpanzees (Lonsdorf et al 2020 ) and baboons (Carter et al 2020 ), although Carter et al ( 2020 ) note that carrying by non-mothers is usually of short duration, as in our sibling vervet monkey. The learning to mother hypothesis has been proposed to explain why some non-mothers carry dead infants: behaving maternally towards even a dead infant can contribute toward gaining skills required to be a competent mother (Warren and Williamson 2004 ).…”
Section: Discussionmentioning
confidence: 61%
“…It has been suggested that extended carrying occurs especially in places with more extreme climates (e.g. the habitats of mountain gorillas and geladas), or during dry seasons (Biro et al 2010 ), the conditions of which may slow the decomposition of a body (Fashing et al 2011 ), although a recent analysis found no evidence that chimpanzees carried infant corpses for longer in the dry season (Lonsdorf et al 2020 ). Beminde’s infant was born relatively early in the birth season (October), when climatic conditions were fairly dry compared to later in the season (November–December), which may have helped mummify the body.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations